Analysis of the Effects of Salt Production, Salt Consumption, Per Capita Income, and Exchange Rate on Salt Imports in Indonesia - Ardiwinata, Muhammad Everest; Marseto; Utami, Anisa Fitria (Journal of Economics, Assets, and Evaluation, 2025)
This study aims to analyze the effects of salt production, salt consumption, per capita income, and exchange rate on salt imports in Indonesia. Using a quantitative approach with multiple linear regression methods, data were analyzed over a 14-year period. The results show that salt production and exchange rate have a negative and significant effect on salt imports, while salt consumption has a positive and significant effect. Per capita income shows a positive but statistically insignificant effect. The coefficient of determination (R²) of 71.60% indicates that the independent variables explain most of the variation in salt imports. These findings offer policy implications for the government and industry stakeholders to reduce dependency on salt imports through improved domestic production and adaptive strategies to macroeconomic changes.